Problems of trigeminal neuralgia pathogenesis (statements, contradictions, new approaches). Report 2 - Sapon N. А. (Ukrainian Neurosurgical Journal, 2005)
The theory of stable pain system formation due to central and peripheral segments involving is presented. New perspectives of trigeminal neuralgia (as the cronical neuropathic pain syndrome special case) conservative and surgical treatment are given applying different influence on central and peripheral components of the stable pain system, that has been formed.